A New Model for University-Industry Cooperation: The Case of Chengdu KEDA Ltd. - Peng, S.; Ferreira, F.; Zheng, H. (2016 BAI International Conference, 2016)
In this study, we develop a firm-dominated incremental cooperation model. Following the critical review of current literature and various cooperation models, we identified a number of strengths and shortcomings that form the basis for our framework. The objective of our theoretical model is to contribute to overcome the existing gap within academic literature and theory pertaining to University-Industry (U-I) cooperation (in the context of SMEs) while improving practice in real world context. The uniqueness of the new cooperation model provides a number of benefits over the previous ones in relation to better communication channels and an incremental process that aids in the elimination of risk and cost. Therefore, the probabilities of success for this model, especially in the context of SMEs, should be underlined.